RESPON PERTUMBUHAN TUNAS DARI PROTOCORM-LIKE BODIES MENJADI PLANLET ANGGREK DENDROBIUM HIBRIDA IN VITRO TERHADAP DUA JENIS MEDIA DAN PEMBERIAN TRIPTON - Zasari, Maera; Ramadiana, Sri; Yusnita, Yusnita; Hapsoro, Dwi (JURNAL AGROTROPIKA, 2010)
Dendrobium is great interest because of its high value as a floricultural commodity and a kind of elite herbage plant in Indonesia. An efficient in vitro propagation system via protocorm-like body (PLBs) induction has been developed using one-year-old axillary node explants. The potential of different media and supplements triptone for reliable Dendrobium orchid plantlet regeneration from in vitro PLBs explants were studied. In all two media under investigation, shoot regeneration was achieved when the PLBs were transferred onto solidified MS half strenght and Growmore medium with or without 2 g L-1 triptone supplemented with 15% (v/v) coconut water, 20 g L-1 sucrose, and 2 g L-1 charcoal. The shoots development investigation after three month of culture. 1/2 MS and Growmore media significantly influenced the plantlet regeneration of Dendrobium orchid. Among the media, Growmore showed better performance on shoots and leaves per plantlet, but triptone showed no significant effect on number shoots and leaves. The longest shoots were found in Growmore medium without triptone. Key words: Dendrobium, in vitro, PLBs, planlet, triptone.